2023
DOI: 10.1021/acs.joc.2c02009
|View full text |Cite
|
Sign up to set email alerts
|

DDQ/Fe(NO3)3-Catalyzed Aerobic Synthesis of 3-Acyl Indoles and an In Silico Study for the Binding Affinity of N-Tosyl-3-acyl Indoles toward RdRp against SARS-CoV-2

Abstract: In the present study, we herein report a DDQ-catalyzed new protocol for the synthesis of substituted 3-acylindoles. Being a potential system for virtual hydrogen storage, introduction of catalytic DDQ in combination with Fe(NO3)3·9H2O and molecular oxygen as co-catalysts offers a regioselective oxo-functionalization of C-3 alkyl-/aryllidine indolines even with scale-up investigations. Intermediate isolation, their spectroscopic characterization, and the density functional theory calculations indicate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 75 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…The authors have cited additional references within the Supporting Information (Ref. [23][24][25][26][27][28][29][30]).…”
Section: Supporting Informationmentioning
confidence: 99%
“…The authors have cited additional references within the Supporting Information (Ref. [23][24][25][26][27][28][29][30]).…”
Section: Supporting Informationmentioning
confidence: 99%
“…It was reported that N -sulfonamide indole derivatives possess interesting pharmaceutical activities such as antibacterial and antioxidant, properties, and hence N -tosyl indole–indazole will have significant pharmaceutical properties. However, since naturally occurring indoles lack protecting groups, we also carried out the detosylation of 5a using a solution of 50 mol % sodium hydroxide (NaOH) in methanol–water (1:1) under reflux conditions to obtain the detosylated product 5a′ in 90% yield (Scheme , 5a′ ).…”
mentioning
confidence: 99%